Optimizing Information Technology for Islamic Da’wah and Knowledge Advancement in the Digital Era: An Opinion-Based Literature Perspective - Ahmad Suryan (The Indonesian Institute of Science and Technology Research, 2026)
The rapid development of Information Technology (IT) has fundamentally transformed the landscape of religious communication, education, and knowledge dissemination. In the Islamic context, da’wah and the pursuit of knowledge are core obligations deeply rooted in theological teachings and historical traditions. This article presents an opinion-based academic analysis supported by contemporary literature to examine how IT can be optimized as a strategic instrument for Islamic da’wah and knowledge advancement in the digital era. Drawing on theological foundations, digital pedagogy, and communication studies, the paper proposes a conceptual framework that integrates ethical principles, digital literacy, technological infrastructure, and human resource development. Using a narrative and analytical approach, the article discusses key opportunities and challenges, including digital accessibility, misinformation, ethical dilemmas, and technological addiction. The Results and Discussion section elaborates three interconnected dimensions: theological legitimacy and digital transformation, strategic utilization of IT for da’wah and education, and challenges with proposed optimization strategies. Three analytical tables are presented to synthesize findings across these dimensions. The article argues that optimizing IT for Islamic purposes requires not merely technological adoption but a value-driven, ethically grounded, and collaborative approach involving scholars, educators, technologists, and the Muslim community. The study concludes that IT, when aligned with Islamic ethics and supported by digital literacy, can significantly enhance global da’wah reach and strengthen contemporary Islamic knowledge ecosystems.